2020
DOI: 10.3389/fpubh.2020.00483
|View full text |Cite
|
Sign up to set email alerts
|

How the Media Places Responsibility for the COVID-19 Pandemic—An Australian Media Analysis

Abstract: Global pandemics are likely to increase in frequency and severity, and media communication of key messages represents an important mediator of the behavior of individuals in response to public health countermeasures. Where the media places responsibility during a pandemic is therefore important to study as blame is commonly used as a tool to influence public behavior but can also lead to the subjective persecution of groups. The aim of this paper is to investigate where the media places responsibility for COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 38 publications
3
48
0
2
Order By: Relevance
“…Our media analysis of three Canadian newspapers suggests that in the early days of the pandemic, much of the media attention remain focused on restricting the international travel, extended quarantines, nancial and social hardships, mental health issues, and healthcare and systems capacity coping with the pandemic. The media studies conducted elsewhere reported similar ndings (39,42,43).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our media analysis of three Canadian newspapers suggests that in the early days of the pandemic, much of the media attention remain focused on restricting the international travel, extended quarantines, nancial and social hardships, mental health issues, and healthcare and systems capacity coping with the pandemic. The media studies conducted elsewhere reported similar ndings (39,42,43).…”
Section: Discussionsupporting
confidence: 64%
“…Irwin argues the importance of factchecking and source critique and the need for precision when presenting data and statistics while evaluating the pandemic policies (42). On the contrary Australian media remained objective in reporting the pandemic and government's response (43) by framing the narrative speci cally around "action" and "consequence" (43,44), that were effective for Mad Cow Disease, West Nile virus, and Avian Flu outbreak responses earlier (44).…”
Section: Discussionmentioning
confidence: 99%
“…Information provided in news coverage of COVID-19 in Australia has included reporting of the first cases and deaths and the subsequent rapid spread of the novel coronavirus around the world, accounts of statements, decisions and press conferences held by political leaders and health authorities, strategies to avoid infection, medical controversies and debates and progress towards treatments for COVID-19 and vaccines [5,26,27]. In Australia, very early news reporting (January 2020) focused on the 'mystery Chinese virus' and made continual comparisons to SARS [26].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent news reporting largely focused on the social and economic impacts of the crisis. There was little blame or judgement directed at any social or national groups, although panic buyers did receive some criticism [27].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent news reporting largely focused on the social and economic impacts of the crisis. There was little blame or judgement directed at any social or national groups, although panic buyers did receive some criticism (24).…”
Section: Introductionmentioning
confidence: 99%